Regulation of hemolysin in uropathogenic Escherichia coli fine-tunes killing of human macrophages. Issue 1 (31st December 2018) - M. V. Murthy, Ambika; Phan, Minh-Duy; Peters, Kate M.; Nhu, Nguyen Thi Khanh; Welch, Rodney A.; Ulett, Glen C.; Schembri, Mark A.; Sweet, Matthew J.
ABSTRACT: Uropathogenic E. coli (UPEC) causes the majority of urinary tract infections (UTIs), which are a major global public health concern. UPEC uses numerous mechanisms to subvert the innate immune system, including targeting macrophage functions. We recently showed that some UPEC strains rapidly kill human macrophages via an NLRP3-independent pathway, and also trigger NLRP3-dependent IL-1β processing. In this study, we used random transposon mutagenesis in the reference strain CFT073 to identify UPEC genes that mediate human macrophage cell death. Our approach revealed that the hemolysin A (HlyA) toxin is essential for triggering both cell death and NLRP3 inflammasome-mediated IL-1β release in human macrophages. Random transposon mutagenesis also identified the cof gene, which encodes a poorly characterized phosphatase, as a novel hemolysin regulator; a CFT073 mutant deleted for the cof gene secreted significantly reduced levels of HlyA, had diminished hemolytic activity, and was impaired in its capacity to trigger human macrophage cell death and IL-1β release. Together, our findings reveal that Cof fine-tunes production of hemolysin, an important determinant of both UPEC-mediated inflammasome activation and human macrophage cell death.